PENGARUH KEGIATAN ASISTENSI MENGAJAR TERHADAP TINGKAT KEMATANGAN KARIER MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Rwanda, Patricia; Genjik, Bambang; Witarsa, Witarsa (Universitas Tanjungpura, 2023)
This research was conducted to determine: 1). Teaching Assistance Activities of FKIP UNTAN Economic Education students, 2). Career maturity level of FKIP UNTAN Economic Education students, and 3). The influence of Teaching Assistance activities on students' career development to become teachers. Determining the type of approach to research uses a quantitative approach with the type of influence study. The sample taken in the research was the same as the population because it used a census technique, namely 86 respondents who were Economics Education students taking part in teaching assistance class 3. The analysis used in this research was simple linear regression. The independent variable (X) in this research is teaching assistance activities and the dependent variable (Y) is career maturity. Based on the results of the research conducted, it can be stated that (1) Teaching assistance activities for Economic Education students at FKIP UNTAN obtained an average percentage of ability for Economic Education students in teaching assistance activities of 78.66% with a high category; (2) The career maturity of FKIP UNTAN Economic Education students obtained an average percentage of 73.51% in the high category; and (3) based on the findings of the two components above, it can be determined that teaching assistance activities have a significant influence on the career maturity of FKIP UNTAN Economic Education students, with a determinant coefficient value or influence of 42.1% and the remaining 57.9% is influenced by factors others that were not determined and discussed in this study